STATISTIC EVALUATION OF PRACTICAL DEFICIENT CLINICAL CASES - Ramona Diana Feier; Doriana Forna; Norina Consuela Forna (Romanian Dental Association for Education, 2013)
Aim of the study This study aims,at identifying throughout statistic evaluation,the means of rehabilitation of partially edentulous patient. Material and methods The study group was represented by patients with ages between 29 and 82 years ,diagnosed with partial edentation , treated in Clinical Base for Learning from the School of Dental Medicine,Iasi,between 2011-2013,evaluated clinically and paraclinicaly. Results The results optained subsequent to clinical and paraclinical evaluation show the status of partial edentoulous patient,both general and local.